Deutsche und österreichische Rechtsterminologie an ausgewählten Beispielen aus dem Bereich des Familienrechts - Aneta Łosińska (Linguistische Treffen in Wrocław)
This article deals with differences in German and Austrian legal terminology. German is the official language in both Austria and Germany. Despite this fact, the legal language of the two countries differs considerably. This applies above all to specialised terminology. Since Austria’s accession to the European Union, i.e. since 1995, EU law written in German has applied in Austria, the German-language version of which primarily contains the legal terminology of the Federal Republic of Germany. This leads to serious problems in translation – as only ‘German’ terms are given in dictionaries, and the translators are generally unaware of the differences. On the one hand, this poses problems for Austrians who have to translate foreign-language texts into their ‘mother tongue’, but even greater problems for language mediators at the international level, who are confronted with legal and administrative texts from Austria. This article presents the results of an analysis of selected examples of German and Austrian legal terminology in the field of family law. The analysis was limited to lexical peculiarities that can be found in both national legal systems. The examples analysed show that legal language or legal terminology must always be seen in the context of the legal system in which it is embedded. Therefore, a comparison of terminology always means a comparison of law.